Navigating drugs at university: normalisation, differentiation and drift?. Issue 4 (8th October 2018) - Patton, David
Abstract : Purpose: Whilst drug use appears to be common amongst university students, the purpose of this paper is to move beyond mere drug prevalence, and use the six dimensions of normalisation to better understand the role and place drugs play in the lives of university students. Design/methodology/approach: In total, 512 students completed a student lifestyle survey. Findings: A differentiated normalisation is occurring amongst different student groups; the social supply of drugs is common, and some users are "drifting" into supply roles yet such acts are neutralised. Students are "drug literate" and have to navigate drugs, and their consumption, availability and marketing, as part of their everyday student life. Practical implications: Student drug use is not homogenous and very little is known about the nuances and diversity of their use/non-use beyond prevalence data. Qualitative studies are needed to better understand the processes of differentiated normalisation and social supply. Originality/value: This is the first study in the UK to use the six dimensions of normalisation amongst a sample of university students.